(untitled) (Al-Qamar, 2023)
When Hazrat Muhammad (ﷺ) was asked to relate his views about poetry. He (P.B.U.H) replied: هُوَ کَلَامٌ فَحَسَنُهٗ حَسَنٌ وَقَبِیْحُهُ قَبِیْحٌ[i] Poetry is a speech, and if it’s excellent, it’s correct. If poetry is awful, it is incorrect (prohibited)’’. It becomes illuminatingly clear that poetry is the best means to unveil and Express emotions. Love for Hazrat Muhammad (ﷺ) is the embodiment of unshakeable belief in Islam. The Muslim poets have transformed deep love and reverence for Hazrat Muhammad (ﷺ) into poetic form. Hafiz Mazhar-Ul-Din Mazhar’s poetry marks a distinguished status in this regard. He is one of the most celebrated Poets of 20th century. Mazhar-Ul-Din’s works consist both of prose and poetry. The captivating use of the genres of poetry in his exceedingly exotic quality. He portrayed and beautifully delineated Hazrat Muhammad’s (ﷺ) life and his personality in his poetry. Abundant use of (تلمیح) has been noted in the works of poets. Hafiz Sahab has also employed talmih (تلمیح) repeatedly in his works. The research-oriented critique of (تلمیحات) regarding Mazhar’s poetry has been presented in the subject under consideration..